Determinant Profitability and Implications on the Value of the Company: Empirical Study on Banking Industry in IDX - Luqman Hakim (International Journal of Economics and Financial Issues, 2018)
This research is intended to test several factors affecting profitability that can impact the value of the company in the banking industry in Indonesia. Exogenous variables used are company growth, capital adequacy ratio (CAR), nonperforming loan, loan to deposit ratio, operational cost to operating income, deposit growth, with endogenous variable in first research model using return on assets while in second research model using company value. The type of data used onto this study is secondary data in the form of time series and cross section with research objects of banking companies in Indonesia stock exchange (BEI) during the period 2010–2015 with a population of 42 companies. Of the population selected as a sample of 27 companies. Analysis of research results using multiple regression at the level of α = 10% with Eviews9 application which resulted random effect model estimation. The result of the research with partial test of the first research model is the variable of company growth significantly influence to profit return on assets (ROA) with positive correlation. Variable CAR, non-performing loan, DPK growth significantly affects ROA profitability with negative correlation. The company with the highest level of sensitivity is Bank International Indonesia with BNII trading code, while the smallest sensitivity is Bank MNC International with BABP trading code. This research model can be used significantly and the exogenous variable can explain the endogenous variable of 25.2%. In the second research model, the partial test produced non-performing loan variable significantly influences the negative correlation between corporate value, as well as the growth of DPK significantly affects the firm’s value with positive correlation, but ROA profitability as intervening variable does not function as mediation to explain to the value of the company. Although this second research model can be used significantly but the extent of exogenous variables can only explain the endogenous variable of 10.6%. Keywords: Firm Growth, Capital Adequacy Ratio, Nonperforming Loan, Loan to Deposit Ratio, Operating Cost to Operating Income, Deposit Growth, Return on Assets, Value of the Firm (Tobin’s Q) JEL Classification: G11